(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the knowledge and attitudes regarding emergency contraceptive pills (ECPs) and identify associated factors among students at Phenikaa University in 2025. Methods: A cross-sectional study was conducted involving 246 students at Phenikaa University. Results: The findings revealed that 67.9% of students were aware of ECPs, while 63.8% demonstrated good knowledge and 85.0% held positive attitudes. Multivariate regression analysis confirmed that several factors were statistically significantly associated with knowledge levels (p < 0.05): gender (AOR = 2.66; 95% CI: 1.38 – 5.13), being a third-year student (AOR = 4.05; 95% CI: 1.55 – 14.32), a fourth-year student (AOR = 4.2; 95% CI: 1.1 – 16.07), or a student in their fifth year or above (AOR = 4.92; 95% CI: 1.07 – 22.52), and being enrolled in health-related majors (AOR = 2.28; 95% CI: 1.02 – 5.09). In contrast, no statistically significant associations were found between attitudes and any independent variables in the multivariate analysis. Conclusion: Students’ knowledge and attitudes toward ECPs are at a fair level; however, knowledge gaps persist that need to be addressed through tailored and accessible reproductive health communication and education programs